2010
DOI: 10.1186/1749-8090-5-65
|View full text |Cite
|
Sign up to set email alerts
|

Acute left main coronary artery thrombosis due to cocaine use

Abstract: It is common knowledge that cocaine has been linked to the development of various acute and chronic cardiovascular complications including acute coronary syndromes. We present a young, male patient, drug abuser who underwent CABG due to anterolateral myocardial infarction. Our presentation is one of the very rare cases reported in literature regarding acute thrombosis of left main coronary artery related to cocaine use, in a patient with normal coronary arteries, successfully operated. Drug-abusers seem to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…The acute use of cocaine has been demonstrated in the literature to result in coronary vasospasms but has not been well documented to result in thrombus formation and acute coronary syndrome (ACS) weeks after its effects have worn off. Coleman et al were the first to mention a relationship between ACS and cocaine use [ 1 , 2 ]. However, it has been reported that the risk of ACS is increased 24-fold during the first hour after cocaine use in patients with normal coronary arteries [ 1 , 3 ], thus making this case a very unusual presentation of ACS as a result of a history of cocaine usage.…”
Section: Introductionmentioning
confidence: 99%
“…The acute use of cocaine has been demonstrated in the literature to result in coronary vasospasms but has not been well documented to result in thrombus formation and acute coronary syndrome (ACS) weeks after its effects have worn off. Coleman et al were the first to mention a relationship between ACS and cocaine use [ 1 , 2 ]. However, it has been reported that the risk of ACS is increased 24-fold during the first hour after cocaine use in patients with normal coronary arteries [ 1 , 3 ], thus making this case a very unusual presentation of ACS as a result of a history of cocaine usage.…”
Section: Introductionmentioning
confidence: 99%
“…-гиперкоагулопатиями, обусловленными аутоим-мунными/системными поражениями с развитием STEMI у молодых женщин (54,5%) [33]; приемом контрацепти-вов; нефротическим синдромом; -употреблением амфетамина/наркотиков с развити-ем ИМ в 6% [8,19].…”
unclassified
“…Доминирующие предикторы риска ОКС у молодых мужчин: курение больше 1 пачки/день (77%), отягощен-ный семейный анамнез ИБС (55%), дислипидемия (44%), гиподинамия, избыточная масса тела/ожирение (39/20%), амфетамины/наркотики; стрессы/подростковая агрессия [7,8,13,18,26,43,47,50,58,61]. У молодых женщин к основным предикторам относят: ожирение, метаболиче-ский синдром, аутоиммунные/системные заболевания, прием контрацептивов, спонтанная диссекция КА при родах/в раннем послеродовом периоде.…”
unclassified
See 1 more Smart Citation
“…[20][21][22] Cocaine activates circulating platelets by increasing expression of platelet factor 4, thromboglobulin B, and P-selectin. 23,24 Elevated levels of C-reactive protein, von Willebrand factor, and fibrinogen also affect coagulation, with no compensatory increase in fibrinolytic activity.…”
Section: Prothrombotic Effectsmentioning
confidence: 99%